Concrete for electromagnetic shielding and preparation method and application thereof

By using nickel-iron slag-polythiophene-polyurethane composite hydrogel, vitrified microbeads and diatomaceous earth in concrete, the problems of weak conductivity and uneven pore distribution of existing concrete are solved, and high strength is achieved and excellent electromagnetic shielding performance.

CN119409456APending Publication Date: 2025-02-11GUANGZHOU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411486200.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing concrete has problems such as weak conductivity, uneven pore distribution and early hydration prolongation in improving electromagnetic wave shielding performance, making it difficult to have high strength and excellent electromagnetic shielding performance.

Method used

Ni-iron slag-polythiophene-polyurethane composite hydrogel is used as the conductive phase, and the pore structure is regulated by introducing vitrified microbeads and diatomaceous earth, forming a conductive polymer continuous network with low permeability threshold, enhancing the conductivity of concrete and strength.

Benefits of technology

It realizes concrete with excellent electromagnetic shielding performance, high compressive strength and low cost. It is suitable for large-scale industrial applications, and is simple in preparation and easy to obtain raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098765180000041
    Figure BDA0005098765180000041
  • Figure BDA0005098765180000051
    Figure BDA0005098765180000051
  • Figure BDA0005098765180000061
    Figure BDA0005098765180000061
Patent Text Reader

Abstract

The invention discloses concrete for electromagnetic shielding and a preparation method and application thereof. The concrete for electromagnetic shielding comprises the following components in parts by mass: 100 parts of Portland cement; 0.5 to 3 parts of a nickel iron slag-polythiophene-polyurethane composite hydrogel; 10 to 20 parts of glass beads; 8 to 15 parts of diatomite; 190 to 220 parts of fine aggregate; 280 to 340 parts of coarse aggregate; and 1.5 to 4 parts of a water reducing agent. The preparation method of the concrete for electromagnetic shielding is very simple, all the components are uniformly mixed in batches, and then molding and curing are performed to obtain the concrete for electromagnetic shielding. The concrete for electromagnetic shielding has the advantages of being excellent in electromagnetic shielding performance, high in strength, low in cost and the like, the preparation method is simple, raw materials are easy to obtain, and the concrete is suitable for large-scale industrial application in the field of electromagnetic shielding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electromagnetic shielding, and in particular to concrete for electromagnetic shielding, a preparation method and application thereof. Background Art

[0002] Concrete has the advantages of high strength, abundant raw materials, low price, and simple preparation. It is an irreplaceable basic building material. In recent years, with the popularization of electronic devices and the development of wireless communication technology, the problem of electromagnetic wave pollution has become increasingly serious. In addition, electromagnetic wave detection is also one of the important means to judge the potential economic value and military value of buildings. Therefore, it is necessary to reduce the detectability of electromagnetic waves in key buildings to ensure national security. Therefore, it is urgent to improve the electromagnetic wave shielding performance of concrete used in certain specific fields.

[0003] Research shows that the key to electromagnetic wave protection or shielding is to reflect or lose the intruding electromagnetic waves well. At present, the commonly used method is to enhance the conductivity of concrete or introduce a cavity structure, introduce a metal mesh as a shielding layer, and then form a multi-layer composite wall with the concrete matrix layer to enhance the protection performance against electromagnetic pulses.

[0004] In order to avoid the problem of weak interlayer interface bonding, conductive pathways can be constructed in the concrete matrix by using conductive phases such as steel fibers, carbon fibers, and carbon nanotubes, thereby achieving multi-level reflection and loss of invading electromagnetic waves. However, the density difference between steel fibers and carbon fibers and cement-based materials is huge, which easily leads to segregation and stratification, resulting in uneven distribution of conductive phases and weak overall conductivity of concrete. The introduction of carbon nanotubes is also prone to agglomeration and uneven dispersion, and in order to achieve high conductivity, a higher carbon nanotube content is usually required.

[0005] In order to utilize the multiple reflection characteristics of the cavity to protect against incident electromagnetic waves, the number and relative proportion of open and closed pores can be regulated by introducing cationic, anionic and nonionic surfactants, so that a high reflection loss rate can be achieved in different frequency bands. However, while using surfactants to regulate pore distribution, it also inhibits the early hydration of cementitious materials, prolongs the process of concrete coagulation and hardening, and limits its practical application.

[0006] Therefore, it is of great significance to develop a concrete with both high strength and excellent electromagnetic shielding performance. Summary of the invention

[0007] The purpose of the present invention is to provide concrete for electromagnetic shielding and a preparation method and application thereof.

[0008] The technical solution adopted by the present invention is:

[0009] A concrete for electromagnetic shielding, comprising the following components in parts by mass:

[0010] Portland cement: 100 parts;

[0011] Nickel-iron slag-polythiophene-polyurethane composite hydrogel: 0.5 to 3 parts;

[0012] Vitrified microspheres: 10 to 20 parts;

[0013] Diatomaceous earth: 8 to 15 parts;

[0014] Fine aggregate: 190 to 220 parts;

[0015] Coarse aggregate: 280-340 parts;

[0016] Water reducing agent: 1.5 to 4 parts.

[0017] Preferably, the nickel-iron slag-polythiophene-polyurethane composite hydrogel is prepared by a preparation method comprising the following steps:

[0018] 1) dispersing polythiophene and isocyanate in polyether polyol to obtain a monomer solution;

[0019] 2) dispersing nickel-iron slag in a monomer solution, adding a catalyst to carry out a polymerization reaction, and then washing, drying, grinding and sieving the product to obtain a nickel-iron slag-polythiophene-polyurethane composite hydrogel.

[0020] Preferably, the mass ratio of the polyether polyol, polythiophene, isocyanate and nickel-iron slag is 100:0.2-2.0:120-150:80-180.

[0021] Preferably, the number average molecular weight of the polythiophene in step 1) is 18,000 to 30,000.

[0022] Preferably, the isocyanate in step 1) is at least one of toluene diisocyanate and diphenylmethane diisocyanate.

[0023] Preferably, the polyether polyol in step 1) is at least one of polyethylene glycol and polyoxypropylene glycol.

[0024] Preferably, the number average molecular weight of the polyether polyol in step 1) is 1200-3000.

[0025] Preferably, the particle size of the nickel-iron slag in step 2) is 5 μm to 10 μm.

[0026] Preferably, the amount of the catalyst in step 2) is 0.1% to 1.0% of the mass of the polyether polyol.

[0027] Preferably, the catalyst in step 2) is at least one of triethanolamine and diethanolamine.

[0028] Preferably, the polymerization reaction in step 2) is carried out under a protective atmosphere at a temperature of 50° C. to 80° C., and the reaction time is 30 min to 120 min.

[0029] Preferably, the protective atmosphere is a nitrogen atmosphere.

[0030] Preferably, the drying method in step 2) is vacuum drying or freeze drying.

[0031] Preferably, the nickel-iron slag-polythiophene-polyurethane composite hydrogel in step 2) is in powder form with a particle size of 20 μm to 80 μm.

[0032] Preferably, the particle size of the vitrified microspheres is 15 μm to 35 μm.

[0033] Preferably, the particle size of the diatomaceous earth is 10 μm to 30 μm.

[0034] Preferably, the fine aggregate is at least one of natural river sand and machine-made sand, and has a particle size of 0.075 mm to 4.75 mm.

[0035] Preferably, the coarse aggregate is at least one of granite, diabase and limestone, and has a particle size of 4.75 mm to 26 mm.

[0036] Preferably, the water reducer is a polycarboxylate water reducer.

[0037] A method for preparing the electromagnetic shielding concrete as described above comprises the following steps:

[0038] a) dispersing nickel-iron slag-polythiophene-polyurethane composite hydrogel and a water reducing agent in water to prepare a hydrogel dispersion, and mixing silicate cement, vitrified microspheres, diatomaceous earth, fine aggregate and coarse aggregate to prepare a dry mix;

[0039] b) The hydrogel dispersion, dry mix and water are mixed, and then molded and cured to obtain electromagnetic shielding concrete.

[0040] Preferably, the amount of water in step a) is 22.5% to 35% of the mass of silicate cement.

[0041] Preferably, the amount of water in step b) is 22.5% to 35% of the mass of silicate cement.

[0042] A building material comprising the electromagnetic shielding concrete.

[0043] The principle of the present invention is that the concrete pore solution has a counter-ion shielding effect on the surface of nickel-iron slag in the nickel-iron slag-polythiophene-polyurethane composite hydrogel, and the polythiophene-polyurethane polymer in the nickel-iron slag-polythiophene-polyurethane composite hydrogel will fall off by itself and be evenly distributed in the concrete under stirring, thereby helping to form a continuous network of conductive polymers with a low percolation threshold, enhancing the conductivity of the concrete, and the nickel-iron slag can also be used as a conductive node to further enhance the conductivity of the concrete. The introduction of vitrified microspheres and diatomaceous earth is essentially to use inorganic porous materials to reasonably introduce closed pores and open pores, which can enhance the absorption loss of electromagnetic waves on the one hand, and ensure the stability of the interface bonding with the hydration product matrix on the other hand, reducing the negative effect on the development of concrete strength.

[0044] The beneficial effects of the present invention are as follows: the electromagnetic shielding concrete of the present invention has the advantages of excellent electromagnetic shielding performance, high strength, low cost, etc., and its preparation method is simple and the raw materials are easy to obtain, and it is suitable for large-scale industrial application in the field of electromagnetic shielding.

[0045] Specifically:

[0046] 1) The present invention utilizes the automatic exfoliation of the conductive polymer in the pore solution environment and its redistribution under mechanical stirring, and only a small amount of conductive phase is required to achieve the construction of the conductive network;

[0047] 2) The present invention uses vitrified microspheres and diatomaceous earth to introduce closed pores and open pores, which can not only enhance the absorption and loss of electromagnetic waves, but also stably combine with the hydration product matrix, thereby ensuring the strength development of concrete;

[0048] 3) The electromagnetic shielding concrete of the present invention has an average reflectivity of -10dB to -20dB in the 4GHz to 12GHz frequency band, a 28-day compressive strength of 48MPa to 65MPa, a 28-day dynamic elastic modulus of 32GPa to 42GPa, and a 28-day shrinkage of 120μm / m to 190μm / m, and has excellent electromagnetic shielding performance and high strength;

[0049] 4) The preparation method of the electromagnetic shielding concrete of the present invention is simple, the raw materials are easy to obtain, and it is suitable for large-scale industrial application in the field of electromagnetic shielding. DETAILED DESCRIPTION

[0050] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0051] Embodiment 1:

[0052] A concrete for electromagnetic shielding, the composition of which is shown in the following table:

[0053] Table 1 Composition of a concrete for electromagnetic shielding

[0054]

[0055] Note:

[0056] The preparation method of nickel-iron slag-polythiophene-polyurethane composite hydrogel is as follows:

[0057] 1) adding 2 parts by mass of polythiophene (number average molecular weight of 30,000) to 100 parts by mass of polyethylene glycol (number average molecular weight of 1,500), ultrasonically dispersing for 25 minutes, and then adding 120 parts by mass of toluene diisocyanate, ultrasonically dispersing for 25 minutes to obtain a monomer solution;

[0058] 2) 150 parts by mass of nickel-iron slag (particle size of 5 μm to 10 μm) was added to the monomer solution, magnetically stirred for 10 min, ultrasonically dispersed for 5 min, and then 0.7 parts by mass of triethanolamine was added, magnetically stirred for 5 min, and then placed in a nitrogen atmosphere at 60° C. for 90 min, and then the product was washed with deionized water 5 times, freeze-dried, ground and sieved to obtain nickel-iron slag-polythiophene-polyurethane composite hydrogel (in powder form with a particle size of 20 μm to 80 μm).

[0059] The preparation method of the above electromagnetic shielding concrete is as follows:

[0060] a) adding nickel-iron slag-polythiophene-polyurethane composite hydrogel and polycarboxylate water reducer into water (the amount of water is 30% of the mass of silicate cement), and then ultrasonically dispersing for 5 minutes to prepare a hydrogel dispersion, and dry-mixing fine aggregate and coarse aggregate for 2 minutes, and then adding silicate cement, vitrified microspheres and diatomaceous earth and dry-mixing for 2 minutes to prepare a dry mix;

[0061] b) Add the hydrogel dispersion to the dry mix, stir for 4 minutes, then add water (the amount of water is 30% of the mass of silicate cement) and stir for 3 minutes, then inject into a mold for molding, and then place it in a room temperature environment for curing for 28 days to obtain electromagnetic shielding concrete.

[0062] After testing, the electromagnetic shielding concrete in this embodiment has an average reflectivity of -20dB in the 4GHz to 12GHz frequency band, a 28-day compressive strength of 60MPa, a 28-day dynamic elastic modulus of 40GPa, and a 28-day shrinkage rate of 120μm / m, indicating that it has excellent electromagnetic shielding performance and high strength.

[0063] Note:

[0064] Average reflectivity: Tested in accordance with "GJB 2038A-2011 Radar Absorbing Material (RAM) Reflectivity Test".

[0065] Compressive strength, dynamic elastic modulus and shrinkage rate: tested in accordance with "GB / T 50081-2019 Standard for Test Methods for Physical and Mechanical Properties of Concrete".

[0066] Embodiment 2:

[0067] A concrete for electromagnetic shielding, the composition of which is shown in the following table:

[0068] Table 2 Composition of a concrete for electromagnetic shielding

[0069]

[0070] Note:

[0071] The preparation method of nickel-iron slag-polythiophene-polyurethane composite hydrogel is as follows:

[0072] 1) adding 1.2 parts by mass of polythiophene (number average molecular weight of 25000) to 100 parts by mass of polyoxypropylene glycol (number average molecular weight of 2000), ultrasonically dispersing for 20 minutes, and then adding 130 parts by mass of diphenylmethane diisocyanate, ultrasonically dispersing for 15 minutes to obtain a monomer solution;

[0073] 2) 100 parts by mass of nickel-iron slag (particle size of 5 μm to 10 μm) was added to the monomer solution, magnetically stirred for 8 min, ultrasonically dispersed for 3 min, and then 0.5 parts by mass of diethanolamine was added, magnetically stirred for 5 min, and then placed in a nitrogen atmosphere at 80° C. for 90 min, and then the product was washed 4 times with deionized water, freeze-dried, ground and sieved to obtain nickel-iron slag-polythiophene-polyurethane composite hydrogel (in powder form with a particle size of 20 μm to 80 μm).

[0074] The preparation method of the above electromagnetic shielding concrete is as follows:

[0075] a) adding nickel-iron slag-polythiophene-polyurethane composite hydrogel and polycarboxylate water reducer into water (the amount of water is 25% of the mass of silicate cement), and then ultrasonically dispersing for 2 minutes to prepare a hydrogel dispersion, and dry-mixing fine aggregate and coarse aggregate for 2 minutes, and then adding silicate cement, vitrified microspheres and diatomaceous earth and dry-mixing for 2 minutes to prepare a dry mix;

[0076] b) Add the hydrogel dispersion to the dry mix, stir for 2 minutes, then add water (the amount of water is 25% of the mass of silicate cement) and stir for 4 minutes, then inject into a mold for molding, and then place it in a room temperature environment for curing for 28 days to obtain electromagnetic shielding concrete.

[0077] After testing, the electromagnetic shielding concrete in this embodiment has an average reflectivity of -12dB in the 4GHz to 12GHz frequency band, a 28-day compressive strength of 65MPa, a 28-day dynamic elastic modulus of 42GPa, and a 28-day shrinkage rate of 130μm / m, indicating that it has excellent electromagnetic shielding performance and high strength.

[0078] Embodiment 3:

[0079] A concrete for electromagnetic shielding, the composition of which is shown in the following table:

[0080] Table 3 Composition of a concrete for electromagnetic shielding

[0081]

[0082] Note:

[0083] The preparation method of nickel-iron slag-polythiophene-polyurethane composite hydrogel is as follows:

[0084] 1) adding 0.2 parts by mass of polythiophene (number average molecular weight of 18000) to 100 parts by mass of polyethylene glycol (number average molecular weight of 1800), ultrasonically dispersing for 15 minutes, and then adding 150 parts by mass of toluene diisocyanate, ultrasonically dispersing for 30 minutes to obtain a monomer solution;

[0085] 2) 80 parts by mass of nickel-iron slag (particle size of 5 μm to 10 μm) were added to the monomer solution, magnetically stirred for 8 minutes, ultrasonically dispersed for 3 minutes, and then 0.2 parts by mass of triethanolamine were added, magnetically stirred for 5 minutes, and then placed in a nitrogen atmosphere at 50° C. for 90 minutes, and then the product was washed with deionized water for 3 times, and then freeze-dried, and then ground and sieved to obtain nickel-iron slag-polythiophene-polyurethane composite hydrogel (in powder form with a particle size of 20 μm to 80 μm).

[0086] The preparation method of the above electromagnetic shielding concrete is as follows:

[0087] a) adding nickel-iron slag-polythiophene-polyurethane composite hydrogel and polycarboxylate water reducer into water (the amount of water is 32% of the mass of silicate cement), and then ultrasonically dispersing for 5 minutes to prepare a hydrogel dispersion, and dry-mixing fine aggregate and coarse aggregate for 4 minutes, and then adding silicate cement, vitrified microspheres and diatomaceous earth and dry-mixing for 3 minutes to prepare a dry mix;

[0088] b) Add the hydrogel dispersion to the dry mix, stir for 3 minutes, then add water (the amount of water is 32% of the mass of silicate cement) and stir for 3 minutes, then inject into a mold for molding, and then place it in a room temperature environment for curing for 28 days to obtain electromagnetic shielding concrete.

[0089] After testing, the electromagnetic shielding concrete in this embodiment has an average reflectivity of -10dB in the 4GHz to 12GHz frequency band, a 28-day compressive strength of 52MPa, a 28-day dynamic elastic modulus of 35GPa, and a 28-day shrinkage rate of 190μm / m, indicating that it has excellent electromagnetic shielding performance and high strength.

[0090] Embodiment 4:

[0091] A concrete for electromagnetic shielding, the composition of which is shown in the following table:

[0092] Table 4 Composition of a concrete for electromagnetic shielding

[0093]

[0094] Note:

[0095] The preparation method of nickel-iron slag-polythiophene-polyurethane composite hydrogel is as follows:

[0096] 1) adding 0.3 parts by mass of polythiophene (number average molecular weight of 25000) to 100 parts by mass of polyethylene glycol (number average molecular weight of 1200), ultrasonically dispersing for 15 minutes, and then adding 130 parts by mass of toluene diisocyanate, ultrasonically dispersing for 15 minutes to obtain a monomer solution;

[0097] 2) 120 parts by mass of nickel-iron slag (particle size of 5 μm to 10 μm) was added to the monomer solution, magnetically stirred for 6 min, ultrasonically dispersed for 3 min, and then 0.4 parts by mass of triethanolamine was added, magnetically stirred for 5 min, and then placed in a nitrogen atmosphere at 50° C. for 90 min, and then the product was washed with deionized water 3 times, and then freeze-dried, and then ground and sieved to obtain nickel-iron slag-polythiophene-polyurethane composite hydrogel (in powder form, with a particle size of 20 μm to 80 μm).

[0098] The preparation method of the above electromagnetic shielding concrete is as follows:

[0099] a) adding nickel-iron slag-polythiophene-polyurethane composite hydrogel and polycarboxylate water reducer into water (the amount of water is 30% of the mass of silicate cement), and then ultrasonically dispersing for 4 minutes to prepare a hydrogel dispersion, and dry-mixing fine aggregate and coarse aggregate for 4 minutes, and then adding silicate cement, vitrified microspheres and diatomaceous earth and dry-mixing for 2 minutes to prepare a dry mix;

[0100] b) Add the hydrogel dispersion to the dry mix, stir for 3 minutes, then add water (the amount of water is 30% of the mass of silicate cement) and stir for 2 minutes, then inject into a mold for molding, and then place it in a room temperature environment for curing for 28 days to obtain electromagnetic shielding concrete.

[0101] After testing, the electromagnetic shielding concrete in this embodiment has an average reflectivity of -12dB in the 4GHz to 12GHz frequency band, a 28-day compressive strength of 48MPa, a 28-day dynamic elastic modulus of 32GPa, and a 28-day shrinkage rate of 160μm / m, indicating that it has excellent electromagnetic shielding performance and high strength.

[0102] Embodiment 5:

[0103] A concrete for electromagnetic shielding, the composition of which is shown in the following table:

[0104] Table 5 Composition of a concrete for electromagnetic shielding

[0105]

[0106] Note:

[0107] The preparation method of nickel-iron slag-polythiophene-polyurethane composite hydrogel is as follows:

[0108] 1) adding 1 part by mass of polythiophene (number average molecular weight of 25000) to 100 parts by mass of polyethylene glycol (number average molecular weight of 1200), ultrasonically dispersing for 20 minutes, and then adding 140 parts by mass of toluene diisocyanate, ultrasonically dispersing for 20 minutes to obtain a monomer solution;

[0109] 2) 80 parts by mass of nickel-iron slag (particle size of 5 μm to 10 μm) were added to the monomer solution, magnetically stirred for 10 min, ultrasonically dispersed for 4 min, and then 0.2 parts by mass of triethanolamine were added, magnetically stirred for 5 min, and then placed in a nitrogen atmosphere at 60 ° C for 90 min, and then the product was washed with deionized water for 3 times, and then freeze-dried, and then ground and sieved to obtain nickel-iron slag-polythiophene-polyurethane composite hydrogel (in powder form with a particle size of 20 μm to 80 μm).

[0110] The preparation method of the above electromagnetic shielding concrete is as follows:

[0111] a) adding nickel-iron slag-polythiophene-polyurethane composite hydrogel and polycarboxylate water reducer into water (the amount of water is 33% of the mass of silicate cement), and then ultrasonically dispersing for 4 minutes to prepare a hydrogel dispersion, and dry-mixing fine aggregate and coarse aggregate for 4 minutes, and then adding silicate cement, vitrified microspheres and diatomaceous earth and dry-mixing for 3 minutes to prepare a dry mix;

[0112] b) Add the hydrogel dispersion to the dry mix, stir for 4 minutes, then add water (the amount of water is 33% of the mass of silicate cement) and stir for 3 minutes, then inject into a mold for molding, and then place it in a room temperature environment for curing for 28 days to obtain electromagnetic shielding concrete.

[0113] After testing, the electromagnetic shielding concrete in this embodiment has an average reflectivity of -14dB in the 4GHz to 12GHz frequency band, a 28-day compressive strength of 55MPa, a 28-day dynamic elastic modulus of 34GPa, and a 28-day shrinkage rate of 140μm / m, indicating that it has excellent electromagnetic shielding performance and high strength.

[0114] Comparative Example 1:

[0115] A concrete, which is exactly the same as the concrete for electromagnetic shielding in Example 1, except that the quality of "nickel-iron slag-polythiophene-polyurethane composite hydrogel" is replaced by "nickel-iron slag-polyurethane composite hydrogel".

[0116] Note:

[0117] The preparation method of nickel-iron slag-polyurethane composite hydrogel is as follows:

[0118] 1) adding 120 parts by mass of toluene diisocyanate to 100 parts by mass of polyethylene glycol (number average molecular weight is 1500), and ultrasonically dispersing for 25 minutes to obtain a monomer solution;

[0119] 2) 150 parts by mass of nickel-iron slag (particle size of 5 μm to 10 μm) was added to the monomer solution, magnetically stirred for 10 min, ultrasonically dispersed for 5 min, and then 0.7 parts by mass of triethanolamine was added, magnetically stirred for 5 min, and then placed in a nitrogen atmosphere at 60 ° C for 90 min, and then the product was washed with deionized water 5 times, and then freeze-dried, and then ground and sieved to obtain nickel-iron slag-polyurethane composite hydrogel (in powder form with a particle size of 20 μm to 80 μm).

[0120] After testing, the average reflectivity of the concrete in this comparative example in the 4GHz to 12GHz frequency band is -6dB, the 28-day compressive strength is 58MPa, the 28-day dynamic elastic modulus is 39GPa, and the 28-day shrinkage rate is 130μm / m, indicating that the lack of polythiophene will greatly reduce the average reflectivity of the concrete (that is, it will significantly affect the electromagnetic shielding performance of the concrete).

[0121] Comparative Example 2:

[0122] A concrete, which is exactly the same as the electromagnetic shielding concrete in Example 2 except that the amount of vitrified microspheres is adjusted from "12 parts by mass" to "3 parts by mass" and the amount of diatomaceous earth is adjusted from "12 parts by mass" to "3 parts by mass".

[0123] After testing, the concrete in this comparative example has an average reflectivity of -4dB in the 4GHz to 12GHz frequency band, a 28-day compressive strength of 55MPa, a 28-day dynamic elastic modulus of 30GPa, and a 28-day shrinkage of 190μm / m, indicating that too low a dosage of glass microspheres and diatomaceous earth will not only greatly reduce the average reflectivity of the concrete (i.e., it will significantly affect the electromagnetic shielding performance of the concrete), but also have a great impact on the strength of the concrete.

[0124] Comparative Example 3:

[0125] A concrete, which is exactly the same as the electromagnetic shielding concrete in Example 3 except that the quality of "nickel-iron slag-polythiophene-polyurethane composite hydrogel" is replaced by "slag (particle size of 10μm to 30μm)".

[0126] After testing, the concrete in this comparative example has an average reflectivity of -7dB in the 4GHz to 12GHz frequency band, a 28-day compressive strength of 54MPa, a 28-day dynamic elastic modulus of 34GPa, and a 28-day shrinkage of 200μm / m, indicating that replacing the nickel-iron slag-polythiophene-polyurethane composite hydrogel with slag will greatly reduce the average reflectivity of the concrete (i.e., it will significantly affect the electromagnetic shielding performance of the concrete).

[0127] Comparative Example 4:

[0128] A concrete, which is completely the same as the electromagnetic shielding concrete in Example 1 except that it does not contain "nickel-iron slag-polythiophene-polyurethane composite hydrogel".

[0129] After testing, the average reflectivity of the concrete in this comparative example for the 4GHz to 12GHz frequency band is -2dB, the 28-day compressive strength is 62MPa, the 28-day dynamic elastic modulus is 42GPa, and the 28-day shrinkage is 290μm / m, indicating that not adding nickel-iron slag-polythiophene-polyurethane composite hydrogel will not only greatly reduce the average reflectivity of the concrete (that is, it will significantly affect the electromagnetic shielding performance of the concrete), but will also cause the shrinkage rate of the concrete to increase significantly.

[0130] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A concrete for electromagnetic shielding, characterized in that: The composition comprises the following components in parts by weight: Portland cement: 100 parts; Nickel-iron slag-polythiophene-polyurethane composite hydrogel: 0.5 to 3 parts; Vitrified microspheres: 10 to 20 parts; Diatomaceous earth: 8 to 15 parts; Fine aggregate: 190 to 220 parts; Coarse aggregate: 280-340 parts; Water reducing agent: 1.5 to 4 parts.

2. The electromagnetic shielding concrete according to claim 1, characterized in that: The nickel-iron slag-polythiophene-polyurethane composite hydrogel is prepared by a preparation method comprising the following steps: 1) dispersing polythiophene and isocyanate in polyether polyol to obtain a monomer solution; 2) dispersing nickel-iron slag in a monomer solution, adding a catalyst to carry out a polymerization reaction, and then washing, drying, grinding and sieving the product to obtain a nickel-iron slag-polythiophene-polyurethane composite hydrogel.

3. The electromagnetic shielding concrete according to claim 2, characterized in that: The mass ratio of the polyether polyol, polythiophene, isocyanate and nickel-iron slag is 100:0.2-2.0:120-150:80-180.

4. The electromagnetic shielding concrete according to claim 2, characterized in that: The number average molecular weight of the polythiophene in step 1) is 18000-30000; the isocyanate in step 1) is at least one of toluene diisocyanate and diphenylmethane diisocyanate; the polyether polyol in step 1) is at least one of polyethylene glycol and polyoxypropylene glycol; the number average molecular weight of the polyether polyol in step 1) is 1200-3000.

5. The electromagnetic shielding concrete according to claim 2, characterized in that: Step 2) The particle size of the nickel-iron slag is 5 μm to 10 μm.

6. The electromagnetic shielding concrete according to claim 2, characterized in that: Step 2) The polymerization reaction is carried out under a protective atmosphere at a temperature of 50° C. to 80° C., and the reaction time is 30 min to 120 min.

7. The electromagnetic shielding concrete according to claim 2, characterized in that: Step 2) The nickel-iron slag-polythiophene-polyurethane composite hydrogel is in powder form with a particle size of 20 μm to 80 μm.

8. The electromagnetic shielding concrete according to any one of claims 1 to 7, characterized in that: The particle size of the vitrified microspheres is 15 μm to 35 μm; the particle size of the diatomaceous earth is 10 μm to 30 μm; the fine aggregate is at least one of natural river sand and machine-made sand, with a particle size of 0.075 mm to 4.75 mm; the coarse aggregate is at least one of granite, diabase, and limestone, with a particle size of 4.75 mm to 26 mm.

9. A method for preparing electromagnetic shielding concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: a) dispersing nickel-iron slag-polythiophene-polyurethane composite hydrogel and a water reducing agent in water to prepare a hydrogel dispersion, and mixing silicate cement, vitrified microspheres, diatomaceous earth, fine aggregate and coarse aggregate to prepare a dry mix; b) The hydrogel dispersion, dry mix and water are mixed, and then molded and cured to obtain electromagnetic shielding concrete.

10. A building material, characterized in that: The electromagnetic shielding concrete comprises the electromagnetic shielding concrete according to any one of claims 1 to 8.